2017
DOI: 10.1038/srep40343
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Radiation-tolerant Oxide Dispersion Strengthened Steel and its Microstructure Evolution under Helium-implantation and Heavy-ion Irradiation

Abstract: The world eagerly needs cleanly-generated electricity in the future. Fusion reactor is one of the most ideal energy resources to defeat the environmental degradation caused by the consumption of traditional fossil energy. To meet the design requirements of fusion reactor, the development of the structural materials which can sustain the elevated temperature, high helium concentration and extreme radiation environments is the biggest challenge for the entire material society. Oxide dispersion strengthened steel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 27 publications
2
20
0
Order By: Relevance
“…Lu et al . 53,54 have reported that NO distribution in fine and coarse grains of spark plasma sintered 9Cr ODS alloys having bimodal grain size distribution varies considerably, similar to the present study (see Figs 1 and 3). On the other hand, this is the first study reporting the α′ formation kinetics based on the NO distribution in ODS alloys, to the best of authors’ knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…Lu et al . 53,54 have reported that NO distribution in fine and coarse grains of spark plasma sintered 9Cr ODS alloys having bimodal grain size distribution varies considerably, similar to the present study (see Figs 1 and 3). On the other hand, this is the first study reporting the α′ formation kinetics based on the NO distribution in ODS alloys, to the best of authors’ knowledge.…”
Section: Discussionsupporting
confidence: 90%
“…nm and 5 nm when found at the grain boundary and in the grain interior, respectively, according to prior measurements on these samples from Grigorian and Rupert [62]. The inset in Figure 1 of ZrC precipitates could impact the radiation damage tolerance of the nanocrystalline Cu-Zr samples since precipitates can both limit grain boundary mobility through pinning [39,40] and serve as defect sinks [18,69]. However, both the ordered grain boundary and AIF-containing samples were sourced from the same ball milled powder and contained the same size and density of ZrC precipitates.…”
Section: Methodsmentioning
confidence: 62%
“…Interfaces in the form of phase boundaries have been observed to improve radiation tolerance in oxide dispersion strengthened (ODS) steels by serving as efficient trapping sites, which enhance defect recombination and He dispersion [17][18][19]. Interfaces in the form of grain boundaries are thought to serve as defect sinks by absorbing interstitials, and have been observed to facilitate defect recombination through emission of the stored interstitials to vacancies, annihilating the defect pairs [10,20].…”
Section: Introductionmentioning
confidence: 99%
“…However, to deploy this alloy into a fast reactor environment, the effect of helium addition produced by (n, α) transmutation and subsequent He embrittlement needs to be further studied [14]. There have been a few He implantation studies on various ODS alloys [11,15,16,17,18]. Yamamoto et al observed small-size He bubbles trapped on YTiO clusters during simultaneous neutron and He irradiation of MA957 [15].…”
Section: Introductionmentioning
confidence: 99%